2020
DOI: 10.1080/17434440.2020.1825073
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain technology applications to postmarket surveillance of medical devices

Abstract: Introduction: The amount of mandatory data that needs to be analyzed as part of a medical device postmarket surveillance (PMS) system has grown exponentially in recent times. This is a consequence of increasingly demanding and complex regulatory requirements from Health Authorities, aimed at a better understanding of the medical device safety evaluation. Proactive approaches to PMS processes are becoming more necessary as regulators increase the scrutiny of device safety. New technologies have been explored to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…23 The robust, scalable blockchain paradigm offers a more seamless and more robust approach to sharing international implant performance data between individuals and institutions. 30 Where cross border data risks are a particular concern, patient identifiable data can be shed from the system prior to data exchange. 31 Blockchain technology may also be able to promote transparent research processes.…”
Section: Global Big Data Orthopaedic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The robust, scalable blockchain paradigm offers a more seamless and more robust approach to sharing international implant performance data between individuals and institutions. 30 Where cross border data risks are a particular concern, patient identifiable data can be shed from the system prior to data exchange. 31 Blockchain technology may also be able to promote transparent research processes.…”
Section: Global Big Data Orthopaedic Researchmentioning
confidence: 99%
“…In fact, blockchains can also be deployed to guarantee other important aspects of the orthopaedic supply chain, including the provenance of medical products such as antibiotics 42,43 and implants, 44 protecting the market and patients from counterfeit medical supplies. 45 In a typical blockchain supported supply chain (illustrated in Fig.…”
Section: The Internet Of Things; Connecting Blockchain To Implants and Peoplementioning
confidence: 99%
“…Similarly, with growing attention for postmarket surveillance of medical devices due to stricter regulations, a secure mechanism for verification by designated bodies would promote more adequate review of devices once on the market. 19 With a global race to vaccinate the world, there is an opportunity to leverage blockchain-based supply chains to mitigate inefficiencies, thefts and counterfeits of available vaccines. Similarly, storage temperature and other atmospheric data can be recorded on a blockchain, which provides distributors' and consumers' information about the integrity of the supply chain and can help identify weak points.…”
Section: Reviewmentioning
confidence: 99%
“…For the increasingly important and complex post-marketing surveillance (PMS) of medical devices, increasingly large amounts of data are being generated. It has been shown that a private data-permissioned blockchain with a proof-of-authority consensus mechanism could offer many advantages to the different stakeholders involved in the PMS process, such as providing support with new regulatory initiatives [ 32 ].…”
Section: Applications Of Blockchain In Medical Imagingmentioning
confidence: 99%